A 76 GHz Millimeter-Wave Marine Radar Antenna Design - Ahmed, M. F.; Elshamy, M. A.; Shaalan, A. A. (IAES Indonesian Section, 2024)
In this work, a 76 GHz microstrip antenna array is proposed for usage in the mm-wave Marine radar application. Millimeter-wave radars are commonly used in automotive applications and a lot of effort is made in this way but it is also can be used in marine applications as they work robustly in bad weather conditions such as fog, dust, smog, smoke, and water vapor. So, it will be very helpful in marine applications. The proposed array antenna is a corporate Series feed 24×8 antenna array that has achieved a return loss of -26.4 dB, a gain of 23.5dBi, bandwidth of 5.2 GHz, and sidelobe levels of -21.4 dB in Hplane and -14 dB in E-plane. This antenna array's 3dB angular width equals 10.9 ° in the H-plane and 5.9 ° in the E-plane. That makes it a suitable choice for the mm-wave marine radar antenna. The final design of the antenna is acceptable compared with another previous work, making this design more considerable as will be shown. Also, an antenna array with 3 transmitters and 4 receivers is presented. Each antenna is a 24-element. the Dolph-Chebyshev technique is utilized to taper the patches. The antenna has been manufactured, and the results of the simulation are confirmed by the experimental measurements.